Comparison of Foot Pedal Reaction Time Among Patients with Right or Left Hemiplegia and Able-Bodied Controls. Issue 6 (November 2013) - Pauley, Tim; Ismail, Farooq; Boulias, Chris; Devlin, Michael; Phadke, Chetan P.
Abstract : Background: Although inpatient stroke rehabilitation provides clinicians with the opportunity to prepare patients for continuation of prestroke activities, little is known about the patients' ability to safely resume driving at the point of discharge to the community.Objective: To compare foot pedal response times of 20 stroke patients with right hemiplegia (RH) or left hemiplegia (LH) and 10 controls.Methods : A cross-sectional design was used. Response times were measured using 3 foot pedal operation techniques: (1) right-sided accelerator with right leg operating accelerator and brake, (2) right-sided accelerator with left leg operating accelerator and brake, and (3) left-sided accelerator with left leg operating accelerator and brake. Outcomes included reaction time (RT), movement time (MT), and total response time (TRT).Results: Controls demonstrated faster RT than patients with RH (263 vs 348 ms; P < .001) or LH (316 ms; P < .05) for all conditions, as well as faster MT than patients with RH ( P < .05 for all) but not LH when using the right leg (258 vs 251 ms; P = .82). Controls demonstrated faster TRT than patients with RH ( P < .001 for all) but not LH when using the right leg (515 vs 553 ms; P = .44).Conclusions: When using the nonparetic leg, patients with LH had braking response times comparable to controls, but patients with RH demonstrated significant impairment of both the paretic and nonparetic legs.